Comparisons of Zooplankton Community Structure between with- and without- Pesticide Applications on Rice Fields - Nattaporn Plangklang; Sujeephon Athibai (Diversity, 2021)
Herbicide usage in rice fields over time may have a direct and indirect influence on the biodiversity of the fields. The impacts of herbicide usage on non-target organisms were assessed by examining the species richness and zooplankton density of two rice fields. One was 2.08 hectares in size and had been treated with pesticides during the sampling year (RF-PA). The second field, measuring 1.76 hectares, had received no pesticide treatment (RF-NPA). Every two weeks, zooplankton was quantitatively collected from ten sampling sites in each field. At each station, 20 L of measured water was filtered through a plankton net with a mesh size of 20 µm and preserved in 1% Lugol’s solution. The results revealed that RF-NPA and RF-PA had 112 and 88 species of zooplankton, respectively, with an abundance-based Jaccard index (Jabd) of 0.438. The total zooplankton density in RF-NPA was 24.4 ind./L, significantly higher than the 16.6 ind./L in RF-PA (p < 0.001). The Shannon-Wiener diversity index (H’) and evenness (J) were highest in RF-NPA at the second sampling (3.45 and 0.75, respectively). These results indicate that glyphosate application affects the diversity of species and density of zooplankton in rice fields.